Gynaecological Interventions to Improve Outcomes of Preterm Infants - SANIA PIRZADO, YASMEEN KHATOON, SHABANA BANO SOOMRO, KASHF-UL-KHAIR, BUSHRA NOOR KHUHRO, GHULAM FATIMA (Pakistan Journal of Medical & Health Sciences, 2025)
Background: Preterm infants are at higher risk of health and mental issues and conditions in comparison with full term delivered infants. Specialist follow-up care, involving a multidisciplinary approach, is essential for identifying potential issues early, which can help reduce associated risks. Objective: To assess the outcomes of gyanecological interventions in reducing preterm births. Study Design: Prospective study Place and Duration of Study: Department of Obstetrics & Gynaecology, Pir Abdul Qadir Shah Jeelani Institute of Medical Sciences Gambat from 1st January 2023 to 30th June 2023. Methodology: Two hundred preterm pregnant women based on clinical diagnosis of the pregnant women were enrolled. Preterm pregnant women within the age group of 21 to 44 years were included in this study. Various gynaecological interventions including aspirin usage in 16 weeks, magnesium sulfate and delayed clamping at peripartum, vaginal progesterone, cervical cerclage, cardiotocograph monitoring, caesarean section, antennal corticosteroid, tocolysis as well as continuous positive airway pressure. Kangaroo Mother Care was also provided to the majority of the preterm delivered newborns. Results: Mean age of 30.3±3.5 years and vaginal progesterone and cardiotocograph as well as caesarean section and application of antenatal corticosteroid to bring positive outcomes in the preterm delivery. The interventions of cervical cerclage and tocolysis had more likely to bring negatives outcomes as positive outcomes. The relative risk for Kangaroo Mother Care was 0.95 (0.82 to 0.99). Conclusion: The gynaecological interventions of antenatal corticosteroids, caesarean section, cardiotocograph as well as vaginal progesterone in addition to kangaroo mother care and continuous positive airway pressure usage are associated with significant positive outcomes for preterm infants followed by magnesium sulfate usage as well as delayed clamping. Keywords: Outcome, Preterm infants, Gynaecological intervention.